Modelling and simulation for improving the efficiency of port operations - Lee, Le Ler. (2009)
This paper studies the sea-port operations, particularly, analyzing the possibility in incorporating new technology into the port operations. The developed simulation model effectively incorporate the second model, built using Arena simulation tool.